Dissemination 2.0 - the role of social media in research dissemination - Brandtzæg, Petter Bae (Septentrio Conference Series, 2014)
Dissemination is defined as "the act of diffusing knowledge". The traditional ways of research dissemination, is through the publications of papers and to attend conferences. Traditional dissemination is important, but not very accessible, transparent or visible. However, the principles and possibilities of disseminating research have changed with the introduction of social media – dissemination 2.0. Dissemination 2.0. is about researchers taking control over the dissemination process by the exploitation of social media. Social media is allowing new forms to present research, in conversation, networking and engagement with different audiences, through various media. Over 2 million research scientist are currently using social media (research) tools like Research Gate and Academia.edu, some are also using more broader social media tools such as blogs, SlideShare, Twitter and Facebook. This talk illuminates dissemination 2.0. by presenting some central examples in ways researchers can use social media to disseminate their research.